The Effect of Absorbable Calcium Sulfate on Wear Rates in Ultra-high–Molecular-weight Polyethylene: Potential Implications for Its Use in Treating Arthroplasty Infections. Issue 6 (June 2017) - Lewicki, Kathleen; Prioreschi, Brandon; Koenig, Karl; Keeney, Benjamin; Bartelstein, Meredith; Moucha, Calin; Van Citters, Douglas
Abstract : Introduction: Patients, hospitals, and healthcare systems incur substantial burdens when infections result in total joint revisions. One potential solution to mitigate some of these burdens may be to transition from a two-stage infection treatment to a single-stage procedure. Off-label use of an absorbable calcium sulfate antibiotic carrier has been implemented in single-stage and two-stage procedures globally, with the goal of moving toward more single-stage revisions in the United States. Adverse effects of calcium sulfate on the joint space during articulation are currently unknown. Methods: This study aims to determine the impact of calcium sulfate beads on wear of polyethylene during and following exposure. Two phases of in vitro pin-on-disk testing were conducted. The first phase exposed polyethylene pins to calcium sulfate for 500, 000 cycles of a 2-million cycle test. The second phase examined the wear of pins that were created from retrieved components exposed to calcium sulfate in vivo. Results: No clinically significant difference was observed between the wear rates of the calcium sulfate–exposed polyethylene pins and the control polyethylene pins. Discussion: Preliminary results suggest that a substantial increase in the wear rate of polyethylene is not expected with the addition of calcium sulfate beads during treatment of infection.